Phosphonoformate inhibition of visna virus replication. - Sundquist, B (1979)
Phosphonoformate (PFA) inhibits multiplication of visna virus in sheep choroid plexus cells; a 50% reduction of virus yield was obtained by 20 to 80 microM PFA. Morphological changes, such as syncytial formation and cell degeneration, could be reversibly prevented by PFA. Cell growth was not significantly affected at 500 microM PFA, although prolonged treatment with 2 mM PFA did arrest cell growth. Cell-free reverse transcriptase activity primed with various synthetic template-primers was inhibited about 90% in the presence of 100 microM PFA. The results from kinetic experiments suggested that reverse transcriptase was utilized early but not late in the infection cycle. A structurally related substance, phosphonoacetate, did not inhibit visna virus multiplication and had no inhibitory effect on reverse transcriptase activity at a concentration of 500 microM.